Planted Citrus Regulates the Community and Networks of phoD-Harboring Bacteria to Drive Phosphorus Availability Between Karst and Non-Karst Soils - Xuan Yu; Lulu Feng; Yuan Huang; Yueming Liang; Fujing Pan; Wei Zhang; Yuan Zhao; Yuexin Xiao (Microorganisms)
The phosphorus (P) availability in soils is influenced by microbes, particularly those containing the gene responsible for phosphate solubilization. The present study investigated the community structure, diversity, and co-occurrence networks of phoD-harboring bacteria in karst and non-karst citrus orchard soils across a planting duration gradient, natural forests, and abandoned land, as well as the soil total P (TP) and available P (AP) contents and enzyme activities. The soil AP contents were lower in the karst regions than in the non-karst regions, while the soil organic carbon (C; SOC), exchangeable calcium, and microbial biomass nitrogen (N) contents; alkaline phosphatase (ALP) and β-Glucuronidase activities; and pH had the opposite trends. In addition, the soil AP and SOC contents and the ALP and acid phosphatase (ACP) activities in the karst regions decreased with an increase in the planting years, whereas the AP, TP, and microbial biomass P contents and ACP activities in the non-karst regions increased. The diversity indices and network complexity of phoD-harboring bacteria were higher in the karst regions than in the non-karst regions, with marked community differences between different planting years in the non-karst regions. The soil AP was significantly and positively correlated with the rare genera Pelagicola, Methylobacter, Streptomyces, and Micromonospora in the karst regions and Roseivivax, Collimonas, Methylobacterium, Ralstonia, and Phyllobacterium in the non-karst regions. Structural Equation Modeling showed that citrus cultivation altered the soil pH, SOC, and total N, and, in turn, the phoD-harboring bacterial community structure and diversity, which led to changes in the ALP activity and P availability. Thus, the rare genera of the phoD-harboring bacteria, influenced by the pH and SOC, highly regulated the availability of P in the karst and non-karst citrus orchard soils.